USM TO PRODUCE MORE PROFESSORS IN COMMERCIALISATION EFFORTS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 16 November 2015 Universiti Sains Malaysia (USM) through its Innovation and Commercialisation Office (ICO), in collaboration with USAINS Holdings Sdn Bhd (USAINS) will produce academicians and professors in the field of commercialisation research findings.